Carcharhinus plumbeus - Carneiro, Miguel; Martins, Rogélia; Landi, Monica; Costa, Filipe O. (Zenodo, 2014)
Carcharhinus plumbeus (Nardo, 1827) – Sandbar shark; Tubarão-corre-costa ① , ②③ Arruda (1997) considered a doubtful presence of this species off the Azores. According to Ebert & Stehmann (2013) the occurrence of C. plumbeus in Madeira is possible. : Published as part of Carneiro, Miguel, Martins, Rogélia, Landi, Monica & Costa, Filipe O., 2014, Updated checklist of marine fishes (Chordata: Craniata) from Portugal and the proposed extension of the Portuguese continental shelf, pp. 1-73 in European Journal of Taxonomy 73 on page 12, DOI: 10.5852/ejt.2014.73, http://zenodo.org/record/3866515 : {"references": ["Arruda L. M. 1997. Checklist of the marine fishes of the Azores. Arquivos do Museu Bocage, Nova Serie 3 (2): 3 - 164.", "Ebert D. A. & Stehmann M. F. W. 2013. Sharks, batoids, and chimaeras of the North Atlantic. FAO Species Catalogue for Fishery Purposes no. 7, Food and Agriculture Organization, Rome."]}